Implementation of Accountability and Transparency Principles by Productive Zakat Recipients at Badan Amil Zakat Nasional (BAZNAS) Kota Gorontalo - Fadiya Ramadhani Mallarangeng; Niswatin; Ivan Rahmat Santoso (Universitas KH. Abdul Chalim Mojokerto, 2026)
Productive zakat serves as an empowerment instrument for mustahik at BAZNAS Kota Gorontalo, yet the implementation of accountability and transparency at the recipient level remains challenging. This qualitative descriptive study employs a simple success ratio approach to analyze these principles among five micro-entrepreneur mustahik. Results indicate an accountability ratio of 70% (adequate, strong in fund trustworthiness but weak in administrative recording) and transparency ratio of 100% (excellent, achieved through relational and verbal openness). Grounded in Shariah Enterprise Theory, the vertical dimension (to Allah) is robust, while the horizontal dimension (to the institution) requires strengthening. Findings imply the need for basic financial literacy training and sustained light-touch mentoring to enhance program effectiveness.